Evaluasi Tingkat Kesulitan Belajar Bahasa Inggris Siswa Kelas IV di SDN Karang Tengah 7 - Huliatunisa, Yayah; Hartana, Davina Dewi; Purwanti, Karunia Nurulita; Azhari, Nurfidia; Salsabila, Selvina; Habibah, Siti Ummu (Lembaga Yasin AlSys, 2022)
Learning English is one of the primary school subjects which is an adaptive subject. In the process of learning English, students still experience learning difficulties, namely the difficulties of the four English skills. This study aims to examine the level of difficulty experienced by fourth grade students of SDN Karang Tengah 7 during the process of learning English. This type of research is qualitative research. Through the use of data collection techniques of observation, interviews and documentation. The sample of this research is the fourth grade English teacher and fourth grade students of SDN Karang Tengah 7. The results of this study are obtained showing that students have difficulty learning the four English skills, namely 1) listening ability students still have difficulty distinguishing words, experiencing limited words and students are unable to concentrate because students often talk to other friends, 2) speaking ability because students have difficulty (pronunciation) and vocabulary, 3) reading ability, lack of interest in reading students can also be the cause of student difficulties and 4) Students' writing ability still likes to confuse English letters and arrange sentences so that they have difficulty writing English. From the results of the study it can be concluded that the level of difficulty experienced by the majority of students is pronunciation.